Facile one-step room temperature synthesis of PdAg nanocatalysts supported on multi-walled carbon nanotubes towards electro-oxidation of methanol and ethanol. (10th April 2020) - Makin Adam, Amir Mahmoud; Deng, Min; Zhu, Aimei; Zhang, Qiugen; Liu, Qinglin
Abstract: Pd nanocatalysts still suffer from poor activity and rapid stability degradation due to incomplete oxidation reaction of methanol and ethanol. Herein, we report the facile synthesis of bimetallic PdAg supported on multi-walled carbon nanotube (MWCNT) nanocatalysts prepared via one-step room temperature chemical reduction strategy without additional of any capping agents towards the electrooxidation of methanol and ethanol in alkaline medium. During the synthesis process, reduction reaction between PdCl2, AgNO3 and NaBH4 led to bimetallic PdAg/MWCNT electrocatalysts. The results revealed that the PdAg NPs are uniformly-dispersed on the surface of MWCNT with a well-defined structure, small particle size (5.5 nm) and high surface active area (117.49 m 2 g Pd − 1 ). XPS results showed a strong charge transfer interaction between Pd and Ag atoms on catalytic surface. Cyclic voltammetry (CVs) results demonstrate that as-obtained PdAg/MWCNT electrocatalysts exhibit higher electrochemical activity and long-term durability for methanol and ethanol oxidation than the Pd/C (JM) electrocatalysts. Moreover, Pd3·5 Ag/MWCNT electrocatalyst exhibit higher electrochemical performance in ethanol (3722 mA mg Pd − 1 ) than methanol (1619.52  mA mg Pd − 1 ). This method has shown promising effect as advance strategy for the synthesis of low cost and high-performance Pd-based nanocatalysts, and for large-scale application as well. Graphical abstract: Image 1 Highlights: PdAg/MWCNT nanocatalysts was prepared via one-step room temperature method. MWCNT as support improves the electrochemical performance of both MOR and EOR. The ratio of Ag to Pd has obvious effect on the catalytic activity and durability. Pd3·5 Ag/MWCNT shows significant improvement in the electrochemical performance.